A REVIEW ON AUTHENTICATION AND PRIVACY PROTECTION SCHEMES IN VEHICULAR AD HOC NETWORKS (VANETS) - LAWAL BAGIWA, IDRIS; AMINU MU’AZU , ABUBAKAR; AHMED ZAYYAD, MUSA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Vehicular ad hoc networks (VANETs) is a sort of mobile ad hoc network (MANET) that is designed based on moving vehicles, which are referred to as nodes. The nodes communicate with one another wirelessly, without the need for a network infrastructure that physically connects them. Once the network design has changed, nodes are free to migrate in whatever direction they want as long as the nodes are available to move in that direction. As a result, each node acts as a router, sending traffic to the nodes to which it has been directed. VANET’ popularity however brings with it a variety of issues, including security, routing, and data dissemination. Many solutions have already been presented by different researchers to address these issues, but due to the constant emergence of new threats and attacks, privacy of users must be prioritized above all in VANET. Consequently, a review of authentication, privacy and security solutions presented in different researches have been discussed in this paper, as well as the security services they have studied which were centered towards Authentication, Confidentiality, Availability, and Integrity. In this paper, 10 most relevant schemes were analysed and the result shows that privacy challenges and high computation overhead which causes transmission delays and adds a difficult verification process to VANET communications was the major challenge affecting the VANETs.